Empowerment of Women through Political Participation: Oportunidades’ performance in an indigenous community of Oaxaca. - Avila Jaquez, Carmen (UANL. Facultad de Trabajo Social y Desarrollo Humano, 2009)
This paper reports results on the progress of a government program designed to alleviate poverty in an indigenous community of Oxaca, Mexico. Named Desarrollo Humano Oportunidades, it was designed as a pilot for the entire country. Based on qualitative research results, the paper reports how the program has met challenges and complexities at the local level. These issues may also be present when the program is expanded into other areas. One example can be seen in the secondary objective “empowerment of women”, which has proven a challenge due to the inexperience of many of the women in this community in dealing with political issues and situations. First, the paper offers a brief description of Oportunidades’ operation. Second, it explains the corporate government system (Usos y Costumbres) of an Oaxacan indigenous community and the local actors involved in Oportunidades. Then, it considers the impacts of policy in terms of the relationship between Oportunidades’ actors and the Usos y Costumbres government officials. Finally, it offers some general guidelines to improve the operation of the program in indigenous communities.